PROBABILITAS PERBAIKAN STATUS GIZI ANAK BALITA GIZI BURUK PENGUNJUNG KLINIK GIZI PUSLITBANG GIZI BOGOR SEBELUM DAN PADA SAAT KRISIS EKONOMI - Sihadi Sihadi; Sri Muljati; Amelia Amelia; Susi Suwarti Suwardi (Persagi, 2001)
Probability of Children Severe Malnutrition Improvement on Out-Patient Rehabilitation of Nutrition Clinics In Puslitbang Gizi Bogor at Before and After Economic Crisis.Background: The nutrition clinic of Puslitbang Gizi, Bogor provides a out-patient rehabilitation care package for severely malnourished children during six months. The clinical care is merely aimed at the family itself at home. Due to the changed in economic situation, it is presumed that there will be a difference in nutrition improvement during the crisis as compared to before the crisis.Objective: The objective of the study is to evaluate the effect of out-patient rehabilitation care package by the nutrition clinic of Puslitbang Gizi, Bogor on the improvement of severely malnourished children before and during economic crisis.Methods: The study was conducted using retrospective data of out-patient provided with the rehabilitation care package by the nutrition clinic. Out-patients visiting the nutrition clinic during 1990-1997 represented the